PENDIDIKAN RELIGIUS DALAM PUISI LAUTAN JILBAB KARYA EMHA AINUN NADJIB - Rahma Fatiya; Meilisa Nurhana; Wahyu Dini Septiari (Jurnal Bastra (Bahasa dan Sastra), 2025)
The poem "Lautan Hijab" by Emha Ainun Najib is a literary work that describes spiritual richness and religious values ​​in the context of Indonesian culture. The aim of writing this article is to describe the educational ideology in the poem Lautan Jilbab by Emha Ainun Nadjib. The approach used in this research is descriptive qualitative. The object of this research is the poem Syair Lautan Jilbab by Emha Ainun Najib which will be studied using the theory of hermeneutical studies. The data used is in the form of stanza quotes from several poems contained in Syair Lautan Jilbab by Emha Ainun Najib which express religious values. The data collection technique steps used are in the following three ways: (1) data collection, (2) data reduction, and (3) data presentation. The data analysis technique uses descriptive analytical methods which have the aim of creating a coherent, factual and actual description or picture regarding the facts, nature and relationships between the events studied. The results of the research show that the Poetry Lautan Jilbab by Emha Ainun Najib contains the relationship between religiosity between humans and God, religiosity between humans and humans and religiosity between humans and themselves. The relationship of religiosity that is often found in this poetry is the religious relationship between humans and God.